Biological Evaluation of Phellinsin A Analogues as Chitin Synthase II Inhibitors - Sangku Lee; 김성욱; Eungsoo Kim; Eui-Il Hwang; 정상헌; 이형규 (Bulletin of the Korean Chemical Society, 2007)
KCI Citation Count: 4